Correlation of Transient Elastography With Severity of Cystic Fibrosis–related Liver Disease. Issue 4 (April 2017) - Aqul, Amal; Jonas, Maureen M.; Harney, Sarah; Raza, Roshan; Sawicki, Gregory S.; Mitchell, Paul D.; Fawaz, Rima
Abstract : Objectives: The aim of the study was to evaluate whether liver stiffness measurement (LSM), determined by transient elastography, correlates with presence and severity of liver disease in children and young adults with cystic fibrosis (CF). Methods: Subjects underwent LSM at routine CF visits. Presence and severity of cystic fibrosis liver disease (CFLD) was determined by clinical parameters. Subjects were classified as no CFLD, CFLD without portal hypertension (PHTN), and CFLD with PHTN. LSM was compared with aspartate aminotransferase/platelet ratio index (APRI) as a correlate to severity of CFLD. Results: A total of 249 subjects (53% boys; mean age 14 ± 7 years; 7 [3%] <2 years and 74 [30%] 18–25 years) underwent LSM. Subjects were classified as 158 (64%) with no CFLD, 73 (29%) CFLD without PHTN, and 18 (7%) CFLD with PHTN. The median (interquartile range) LSM was different among the 3 groups: 4.4 (3.8–5.4), 5.1 (4.4–6.3), and 14.1 (8.8–24.8) kPa, respectively, with all pairwise comparisons different from one another ( P  < 0.0001). Similarly, median (interquartile range) APRI was different in groups 1 and 2 compared with CFLD with PHTN: 0.22 (0.17–0.27), 0.24 (0.17–0.33), and 0.53 (0.24–0.84), respectively ( P  < 0.01). Analysis of receiver operating characteristics for discriminating CFLD with PHTN from the other groups resulted in cut-points at 6.2 kPa (LSM) and 0.35 (APRI). LSM was superior to APRI in discriminating CFLD with PHTN from other groups, with areas under the curve 0.91 (LSM) versus 0.78 (APRI) ( P  = 0.05). Conclusions: Liver stiffness, as determined by transient elastography, correlates with the presence and severity of CFLD. Although APRI provided some information regarding severity of liver disease, LSM performed better than APRI in this population.